EVALUATION OF COVID-19 VACCINE EFFECTIVENESS AMONG HEALTHCARE WORKERS USING CASCADE ANALYSIS - Zulkarnain, Bambang Subakti; Kundiman, Eunice Marlene Sicilia; Aina, Lily; Ardianto, Nanda; Meiliani, Fauzul; Rachman, Melinda Putri Amelia; Satryo, Fatimatuz Zahra Oviary; Hapsari, Pharmasinta Putri; Puspitasari, Arina Dery; Rosyid, Alfian Nur; et al. (Jurnal Kesehatan, 2022)
Background: Healthcare workers in Indonesia have been prioritized for vaccination. Nevertheless, fully vaccinated healthcare workers are still at risk of being infected with COVID-19, but will be less likely to develop severe symptoms, be hospitalized or be at risk for death as compared to those who have not been vaccinated. Objectives: This study aims to analyze the incidence of COVID-19 in fully vaccinated healthcare workers. Methods: This cross-sectional study was conducted in 2021. All healthcare workers who have been fully vaccinated, have recovered from COVID-19 (2-4 weeks after vaccination) and able to complete a questionnaire were the participants. The collected data was then analyzed using the cascade method. Results: Based on the 529 collected questionnaires, by using the cascade analysis conclude that the percentage of healthcare workers who have been fully vaccinated was 99%, healthcare workers who have been fully vaccinated and then infected with COVID-19 was 14%, healthcare workers who have been fully vaccinated, infected with COVID-19 and hospitalized was 4%, healthcare workers who have been fully vaccinated, exposed to COVID-19, hospitalized and experienced the long-haul effect of COVID-19 was 0%. Discussion: Health workers are still at risk of being confirmed by COVID-19, because have high risk of being exposed in the workplace. The risk of being confirmed and severity are also influenced by age, gender and comorbidities. Conclusions: Complete vaccinations of healthcare workers did not reduce their risk of being infected with COVID-19, however, it can reduce the severity and the risk of the long-haul effects.